Studi Exploratif, Transformasi Pendidikan dalam Menghadapi Pandemi Corona Virus Disease (COVID-19) - Murwati, Sri Rejeki; Asroriyah, Ni’amah (JPT : Jurnal Pendidikan Tematik, 2020)
The COVID-19 pandemic brought about very significant changes for many countries including Indonesia, especially in the aspect of education. The relationship between education and the Covid pandemic is a change in the flow of education for students marked by a decline in the spirit of learning due to lack of supervision. For this reason, there needs to be a change in educational policies or curricula that are in line with the learning of social distancing systems for students, as well as being efficient and structured. Education transformation is expected later so that it can play a role in overcoming the gaps that occur as a result of the impact of the pandemic. So that the quality of education of the nation's children does not experience lags or declines, on the other hand the period of the COVID-19 pandemic cannot be estimated for its time period.